2011
DOI: 10.1007/s11162-011-9226-3
|View full text |Cite
|
Sign up to set email alerts
|

Going Deep into Mechanisms for Moral Reasoning Growth: How Deep Learning Approaches Affect Moral Reasoning Development for First-year Students

Abstract: The purpose of this paper was to determine the effects of deep approaches to learning on the moral reasoning development of 1,457 first-year students across 19 institutions. Results showed a modest positive relationship between our measures of deep approaches to learning and moral reasoning at the end of the first year of college even after controlling for precollege moral reasoning. After accounting for a host of demographic and relevant student characteristics and for the natural clustering of students, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Our replication of multi-institutional studies suggests that three DAL constructs could be useful for formative assessment, enabling HEIs to track progress across time and possibly across institutions. This study also supports the implicit hypothesis made by Mayhew, Seifert, Pascarella, Nelson Laird, and Blaich (2012) that higher-order, integrative and reflective learning are themselves manifestations of a higher order learning factor; namely, DAL. Our measurement of three DAL constructs differed from that of Campbell and Cabrera's (2014), as it was found the higher-order learning construct was the most reliable indicator of the second order DAL constructs, with fewer measurement errors.…”
Section: Discussionsupporting
confidence: 87%
“…Our replication of multi-institutional studies suggests that three DAL constructs could be useful for formative assessment, enabling HEIs to track progress across time and possibly across institutions. This study also supports the implicit hypothesis made by Mayhew, Seifert, Pascarella, Nelson Laird, and Blaich (2012) that higher-order, integrative and reflective learning are themselves manifestations of a higher order learning factor; namely, DAL. Our measurement of three DAL constructs differed from that of Campbell and Cabrera's (2014), as it was found the higher-order learning construct was the most reliable indicator of the second order DAL constructs, with fewer measurement errors.…”
Section: Discussionsupporting
confidence: 87%
“…These are just two examples in which student affairs practitioners may use critical conversations in which students are asked to: (a) reflect on themselves and situate their ideologies within the broader context of justice in service of the public good, and (b) integrate diverse perspectives as a means to “articulate strategies for grappling with competing hypotheses and points of view” (Mayhew et al., , p. 42). Within a context of challenge and support, these and other approaches can be instrumental in creating transformative learning environments that foster students’ journeys toward moral character development and wise and ethical stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…Research from the WNS found statistically significant relationships between curricular and cocurricular conditions and moral reasoning development for students in a transitional phase of moral reasoning, but these relationships were not significant for students in a consolidated phase (Mayhew, et al, ). For example, influential peer interactions, number of courses that asked students to connect historical, political, and social events, as well as the number of diversity courses were all positively associated with moral reasoning development at the end of the first year of college for students in a transitional phase of moral reasoning but had no effect for students in a consolidated phase.…”
Section: Recognizing Developmental Phasesmentioning
confidence: 90%
See 1 more Smart Citation
“…All independent variables were justified by the extensive literature reviews performed by Mayhew (2002, 2005) and by more recent studies conducted by Mayhew (Mayhew and King 2008;Mayhew and Engberg 2010;Mayhew et al , 2012aMayhew et al , 2012b. This body of research demonstrated the relationships present between moral reasoning development as a dependent measure and gender, pre-college characteristics, curricular experiences, and personal views.…”
Section: Independent Variablementioning
confidence: 99%